(untitled) (KONFERENSIYA, 2025)
The article explains what meta-subject competence is and why it is important in education. It shows that these universal skills—such as thinking, problem-solving, communication, and self-control—help students learn better in all subjects and connect knowledge between them. The article also describes how teachers can develop these skills through joint projects, reflection, and teamwork, helping students form a broader understanding of the world and prepare for real-life situations